KENDAL CITY BRANDING - Ismiati, Dwi; Rachman, Anung; Setiawan, Aris (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2023)
In 2021, Kendal district launched the city branding program through Kendal Handal